Parallel Implementation of Particle Swarm Optimization on FPGA - Matheus Torquato (IEEE Transactions on Circuits and Systems II: Express Briefs, 2019)
This brief proposes a parallel implementation, with fixed point, of the particle swarm optimization (PSO) algorithm on field-programmable gate array (FPGA). Results associated with the processing time and area occupancy on FPGA for several numbers of particles and dimensions were analyzed. Studies concerning the accuracy of the PSO response for the optimization problem using the Rastrigin function were also analyzed for the hardware implementation. The project was developed on the Virtex-6 xc6vcx240t 1ff1156 FPGA.